Manajemen Dalam Perspektif Al Qur’an - Purwaningsih, Yunika (Prosiding University Research Colloquium, 2023)
In managing their daily life. The guidelines and management of references in Islam is to adhere to the Al-Qur'an and Hadith as the basic sources of Islamic teachings which are a reference in solving the problems of Muslims, for all matters relating to human life and all its activities including the management of all items listed management is confirmed in the Qur'an and the hadith of the Prophet Muhammad SAW. In this article, we will describe management in an Islamic view (perspective of the Qur'an) which contains the meaning of management, management functions (planning, organizing, actuating and controlling) and to discuss leadership skills and competencies about what a leader must possess, all of whom related in the view of the Qur'an